Effort-reward imbalance at work and risk of depressive disorders. A systematic review and meta-analysis of prospective cohort studies - Reiner Rugulies; Birgit Aust; Ida EH Madsen (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVE: The aim of this review was to determine whether employees exposed to effort-reward imbalance (ERI) at work have a higher risk of depressive disorders than non-exposed employees. METHODS: We conducted a systematic review and meta-analysis of published prospective cohort studies examining the association of ERI at baseline with onset of depressive disorders at follow-up. The work was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and a detailed study protocol was registered before literature search commenced (Registration number: CRD42016047581). We obtained a summary estimate for the association of ERI with risk of depressive disorders by pooling the study-specific estimates in a meta-analysis. We further conducted pre-defined sensitivity analyses. RESULTS: We identified eight eligible cohort studies, encompassing 84 963 employees and 2897 (3.4%) new cases of depressive disorders. Seven of the eight studies suggested an increased risk of depressive disorders among employees exposed to ERI. The pooled random-effects estimate was 1.49 [95% confidence interval (95% CI) 1.23-1.80, P<0.001], indicating that ERI predicts risk of depressive disorders. The estimate was robust in sensitivity analyses stratified by study quality, type of ERI ascertainment and type depressive disorder ascertainment, respectively. CONCLUSIONS: Employees exposed to ERI were at increased risk of depressive disorder. Future studies on ERI and depressive disorders should examine if this association is stronger or weaker when ERI is measured repeatedly during follow-up and with other methods than self-report or when depressive disorders are ascertained with clinical diagnostic interviews.